PESAN DAKWAH DALAM NOVEL “TERUSIR” KARYA BUYA HAMKA - Yusuf Afandi; Syukrina Damayanti (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2020)
The novel is one of the da’wah media which is routinely used by a preacher to influence its mad`u in the implementation and absorption of its mad’u. One of these is Buya Hamka, a scholar, preacher and writer who has produced phenomenal works that relate daily life to Islamic preaching. In his research, the author examines Buya Hamka's novel, Terusir. The expelled novel recounts the twists in the life of a woman who was expelled from her home and separated from her child, slandered as she fell into the nightlife, and forced to kill someone. The research was qualitative and used qualitative content analysis techniques. The researchers classify the da'wah messages in this novel using the messaging theory of Ali Yafie. The result of this research is that the evicted novel contains messages related to life problems, human problems, scientific problems and theological problems.